Migration of peritoneal catheters in patients undergoing continuous ambulatory peritoneal dialysis - Sakai, Hideto; Suga, Takao; Tanabe, Ryouji; Endoh, Haruko; Nakajima, Keiko; Nakao, Eiichi; Matsumoto, Yukuo; Endoh, Masayuki; Nomoto, Yasuo; Takemura, Fumio (Journal of Japanese Society for Dialysis Therapy, 1993)
It is well-known that outflow obstruction due to encasement of dislocated catheter tips is one of the most serious complications in patients undergoing CAPD. Many researchers have reported the incidence of migration of catheter tips to be 15-20%. In order to clarify the incidence of migration of catheter tips and examine whether there is a relationship between the position of catheter implantation and the occurrence of migration, we evaluated the location of the catheter tip every 2-3 months using plain abdominal X-rays in 100 patients undergoing CAPD with lateral placement of peritoneal catheters in Tokai University Hospital. In all 100 cases, catheter tips were consistently located out of the pelvic cavity in 5 (5%), temporarily out of the pelvic cavity in 19 (19%) and in the pelvic cavity in 76 (76%). Fifty-two cases underwent implantation of a swan-neck catheter on the right side of the umbilicus. The catheter tips were consistently located out of the pelvic cavity in 3 (6%), temporarily out of the pelvic cavity in 12 (23%) and in the pelvic cavity in 37 (71%). Forty-eight cases underwent implantation of a swan-neck catheter on the left side of the umbilicus. The catheter tips were consistently located out of the pelvic cavity in 2 (4%), temporarily out of pelvic cavity in 7 (15%) and in the pelvic cavity in 39 (81%). There was no significant relationship between the position of implantation of the peritoneal catheter and the incidence of migration. Surgical intervention was required 3 cases within 14 days after implantation. There was no relationship between the exit direction of peritoneal catheters and the incidence of migration. In conclusion, we observed that the incidence of migration of peritoneal catheter tips was 24%. However, 2 weeks after the implantation of peritoneal catheters, no patient showed obstruction of in-outflow due to encasement of the omentum or required surgical intervention. No patient showed any relationship between the exit direction of a peritoneal catheter and the incidence of migration.